Pemanfaatan ChatGPT dan Magic School untuk Menunjang Pembelajaran Guru SD Gugus 1 Sandubaya - Sujana, I Made; Nurtaat, Lalu; Fitriana, Eka; La Ode Alfin Haris Munandar; Setiawan, Rozi; Fadhilah, Darin; Putri, Prily Wiske Widiya (Indonesian Journal of Education and Community Services, 2025)
The rapid development of digital technology and artificial intelligence (AI) has brought significant changes to instructional practices, requiring teachers to possess strong digital literacy and the ability to integrate technology into learning design. The workshop on the utilization of ChatGPT and Magic School for elementary school teachers in Gugus 1, Sandubaya District, was conducted to enhance teachers’ understanding and skills in developing AI-based instructional materials. Through interactive lectures, demonstrations, hands-on workshops, and guided mentoring, participants gained comprehensive experience in using AI to generate teaching materials, assessment items, scoring rubrics, and other instructional tools. Survey results indicated that participants found the program highly beneficial, particularly in accelerating the preparation of learning materials and increasing their confidence in implementing technology in the classroom. These findings affirm the substantial potential of AI in supporting teachers' roles as facilitators of 21st-century learning. The activity also opens opportunities for follow-up programs, including advanced training aimed at strengthening teachers’ professional development and digital literacy on an ongoing basis.